Medieval settlement research in the Netherlands in the early twenty-first century - Renes, Hans (Medieval Settlement Research, 2021)
A historiographical and bibliographical review of medieval settlement research in the Netherlands, focusing on work in the early 21st century, and including methodological considerations as well as a region-by-region overview.